Adiponectin Protects Against Cerebral Ischemic Injury Through AdipoR1/AMPK Pathways - Liu, Bin; Liu, Jing; Wang, Jiangong; Sun, Fengjiao; Jiang, Shujun; Hu, Fengai; Wang, Dan; Liu, Dunjiang; Liu, Cuilan; Yan, Haijing (Frontiers in Pharmacology, 2019)
Excitotoxicity induced by excessive NMDA receptor activation underlies the pathology of ischemic injury. Adiponectin (APN) is an adipocyte-derived protein hormone that modulates a number of metabolic processes. APN exerts a wide range of biological functions in the central nervous system. However, the role of adiponectin and its receptors in cerebral ischemia/reperfusion-induced injury and the related mechanisms remain to be clarified. Here we found that APN and APN receptor agonist AdipoRon (APR) were protective against excitotoxicity induced by oxygen and glucose deprivation / reperfusion (OGD/R) and NMDA in primary neurons. Adiponectin receptor 1 (AdipoR1) knock down reversed the protection conferred by either APN or APR. Moreover, the protective effects offered by both APN and APR were compromised by Compound C, an inhibitor of AMPK phosphorylation. Both APN and APR protected the dissipation of the ΔΨm caused by OGD/R. They also up-regulated the PGC-1 expression, which was reversed by Compound C. Furthermore, both APN and APR ameliorated but APN knock out aggravated the infarct volume and neurological deficient induced by transient middle cerebral artery occlusion (tMCAO) in vivo. Taken together, these findings show that APN and APR protect against ischemic injury in vitro and in vivo. The protective mechanism is mainly related to AdipoR1 dependent AMPK phosphorylation and PGC-1alpha up-regulation.